Cochlear implant assessment and candidacy for children with partial hearing. (1st April 2016) - Wilson, Katherine; Ambler, Marette; Hanvey, Kate; Jenkins, Marsha; Jiang, Dan; Maggs, Justine; Tzifa, Konstance
Abstract : Children who have partial hearing (PH) in the low frequencies and profound sensorineural hearing loss in the high frequencies can present a challenge to cochlear implant (CI) teams in terms of referral, assessment, and candidacy. Neither clinical criteria nor optimal timing for implantation has been explored in the literature. Data from both the Hearing Implant Centres of Birmingham Children's Hospital and St Thomas' Hospital indicate that it is clinically appropriate to implant children with PH; they perform better with CIs than with hearing aids, even if their hearing is not fully preserved. We have also found that children need early access to high frequency sound in order to reach their full potential.